A Mycoplasma Genomic DNA Probe using Gated Nanoporous Anodic Alumina. Issue 3 (12th January 2017) - Pla, Luís; Xifré‐Pérez, Elisabet; Ribes, Àngela; Aznar, Elena; Marcos, M. Dolores; Marsal, Lluís F.; Martínez‐Máñez, Ramón; Sancenón, Félix
Abstract: A nanoporous anodic alumina (NAA)‐based sensor system for the detection of Mycoplasma was developed through the implementation of "molecular gates" selective to the presence of this bacterium. The capped support showed a negligible cargo release, while presence of Mycoplasma genomic DNA resulted in the release of rhodamine B fluorescent dye. This sensor system presents a limit of detection of 20 genomic DNA copies⋅μL −1 and was applied to the detection of Mycoplasma bacteria in competitive environments, such as culture cell media. Abstract : Blow the competition away : A nanoporous anodic alumina (NAA)‐based sensor system for the detection of Mycoplasma has been developed. The capped support showed marked release of rhodamine B in the presence of Mycoplasma genomic DNA. The capped support presented a limit of detection of 20 genomic DNA copies μL −1 and was applied to the detection of Mycoplasma in competitive environments (see figure).